Sugar-induced endocytosis of plant 7TM-RGS proteins - Phan, Nguyen; Urano, Daisuke; Srba, Miroslav; Fischer, Lukas; Jones, Alan M (Plant signaling & behavior, 2013)
Plant cells use sugars mainly as a source or store of energy and carbon skeletons for anabolic reactions and for osmotic regulation. The perception of sugars and their responses are rather complex including the heterotrimeric G protein pathway and a seven-transmembrane RGS molecule. Previously, we found that endocytosis of the 7TM-RGS leads to sustained activation of the G protein pathway in the genetic model Arabidopsis. Here we show that other plants possess similar endocytosis systems of the 7TM-RGS proteins. A phosphorylation site essential for the endocytosis is well conserved in land plant 7TM-RGS proteins. In addition, conifer and tobacco 7TM-RGS proteins are internalized in response to sugar. These results indicate a universal mechanism to activate G signaling by endocytosis in plant cells that have 7TM-RGS proteins.
Keywords: Nicotiana; Tracheophyta; Phosphorylation; endocytosis; proteiny huseníčku; sugar signaling; proteiny RGS; fosforylace; Arabidopsis thaliana; Arabidopsis Proteins; cévnaté rostliny; Endocytosis; glukosa; endocytóza; RGS Proteins; Arabidopsis; rostlinné proteiny; tobacco; Glucose; tabák; 7TM-RGS; Plant Proteins; Pinus taeda